2018
DOI: 10.1128/aem.02487-17
|View full text |Cite
|
Sign up to set email alerts
|

Variable Membrane Protein A of Flavescence Dorée Phytoplasma Binds the Midgut Perimicrovillar Membrane of Euscelidius variegatus and Promotes Adhesion to Its Epithelial Cells

Abstract: Phytoplasmas are uncultivated plant pathogens and cell wall-less bacteria and are transmitted from plant to plant by hemipteran insects. Phytoplasmas' circulative propagative cycle in insects requires the crossing of the midgut and salivary glands, and primary adhesion to cells is an initial step towards the invasion process. The flavescence dorée phytoplasma possesses a set of variable membrane proteins (Vmps) exposed to its surface, and this pathogen is suspected to interact with insect cells. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…protein analogous to Vmp1, we could demonstrate that VmpA acts as an adhesin able to bind to insect vector cells in culture and to its midgut perimicrovillar membrane [66,67]. We show here that sequence variations of vmpA and vmpB genes correlate with transmission by insect vectors of different leafhopper subfamilies.…”
Section: Plos Pathogensmentioning
confidence: 65%
See 1 more Smart Citation
“…protein analogous to Vmp1, we could demonstrate that VmpA acts as an adhesin able to bind to insect vector cells in culture and to its midgut perimicrovillar membrane [66,67]. We show here that sequence variations of vmpA and vmpB genes correlate with transmission by insect vectors of different leafhopper subfamilies.…”
Section: Plos Pathogensmentioning
confidence: 65%
“…In the absence of genetic engineering of the uncultivated phytoplasmas, we previously used protein-coated latex beads or recombinant spiroplasmas to mimic phytoplasma surface, and demonstrate that VmpA acts as an adhesin binding to the cells of E. variegatus [66]. Here we found that latex beads had enhanced adhesion to E. variegatus cells in culture and were better retained in E. variegatus and S. titanus midguts, when coated with increasing ratio of FD92 VmpA (cluster II) over PGYA VmpA (cluster I).…”
Section: Plos Pathogensmentioning
confidence: 99%
“…environmental constraints and biological relationships; Daugherty et al ; Lopes et al ) and affect pathogen‐vector interactions at different spatio‐temporal scales and biological organization levels. Some studies suggested the involvement of specific molecular phytoplasma‐ligand interactions in transmission specificity with insect hosts (Suzuki et al ; Galetto et al ; Arricau‐Bouvery et al ). Different types of phytoplasma membrane proteins (MP) are in direct contact with the host environment and have been recognized to play an important role in promoting phytoplasma internalization in insect cells.…”
Section: Introductionmentioning
confidence: 99%
“…P. asteris' amp protein mediates both pathogen crossing of vector gut epithelium and colonization of salivary glands (Rashidi et al 2015), showing the real involvement of these specific molecular interactions in a compatible phytoplasma/vector combination. A similar specific recognition mechanism was recently demonstrated also for FDp and its vector E. variegatus: the variable membrane protein A (vmpA) expressed on the surface of pathogen cells mediates phytoplasma binding to insect cell culture and pathogen retention at the perimicrovillar membrane of vector midgut epithelium (Arricau-Bouvery et al 2018). Lack of such molecular recognition between R. speculum tissues and FDp membrane proteins could explain the low multiplication rate in this host, lack of salivary gland colonization and the consequent inability of transmission.…”
Section: Discussionmentioning
confidence: 70%